Pengaruh Likuditas dan Ukuran Perusahaan Terhadap Penghindaran Pajak Pada Sub Sektor Makanan dan Minuman yang Terdaftar di BEI 2018-2022 - Dwi Intan Erdiyanti; Amor Marundha; Uswatun Khasanah; Nera Marinda Machdar; Cahyadi Husadha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The influence of liquidity and company size on tax avoidance in food and beverage companies listed on the IDX in 2018-2022. The type of data source in this research is the annual financial reports of banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique used was the purposive sampling method and 16 companies were obtained. The data collection technique uses documentation from financial reports published through the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The analysis technique used is panel data regression. In This research uses Eviews 12 software. The results of this research show that: (1) Liquidity has an effect on tax avoidance, (2) Company size has no effect on company value.